PEMBERITAAN POLITAINMENT PASANGAN CALON PRESIDEN DAN WAKIL PRESIDEN PADA PILPRES 2019 DI WWW.VIVA.CO.ID - Dea Rezki Gerastri; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In the 2019 elections, Viva.co.id provided a politainment sub-channel aimed at millennial readers. Even though the 2019 election is a combination of the legislative and presidential elections, the media, including Viva.co.id, highlight the presidential elections as well as in presenting political news. Then, how about the news of politainment of president and vice president candidates in the 2019 Presiden Elections at www.viva.co.id? This research uses quantitative research methods with Gamson and Modigliani framing analysis. So that the analysis of the data was dissected to find out the framing and reasoning device that formed the core packaging of the news of politainment of the president and vice president candidates in the 2019 Presidential Election at www.viva.co.id. In addition, Media Ecology Theory is also used to understand the environment created by Viva.co.id as an online media that has the tagline # 1Newstainment. The results of this research are the news of politainment of the president and vice president candidates in the 2019 Presidential Election on www.viva.co.id packed with framing tools in the headline and supported with metaphorical style, interesting phrases, connotative depictions of explanations and visual illustrations in the contents of news texts. All elements of the framing device are in the news presented by illustrating the attractive humanist side of the candidates. The framing device is supported by the reasoning device as the idea of news justification. Reasoning device are packed with cause-effect explanations, moral messages and framing effects found in the contents of news texts. Packaging news with reasoning tools makes the humanist side of the candidates into something that is true and reasonable because it is in accordance with human values in politicians. The two tools in the Gamson and Modigliani framing analysis produced three main components which explained that Viva.co.id as an online media is a media environment that provides information and communication to the people of Indonesia to influence the way of thinking, feeling, and acting. This influence can be explained in three assumptions in Media Ecology Theory. Keywords: Politainment News. Framing Analysis. Media Ecology. 2019 Presidential Election.